Pengembangan Modul Kimia Berbasis Kontekstual Untuk Membangun Pemahaman Konsep Siswa Pada Materi Asam Basa - Mery Andriani; Muhali Muhali; Citra Ayu Dewi (Hydrogen: Jurnal Kependidikan Kimia, 2019)
Acid-base material is one subject that is considered difficult by students. In addition, students are less able to associate material with a problem or phenomenon in everyday life. The development of a teaching material in the form of modules can be seen as a solution to this problem. This study aims to develop a prototype in the form of developing contextual-based chemical modules to build students' conceptual understanding of acid-base material. This research is a development research with ADDIE model design (Analysis, Design, Development, Implementation, and Evaluation). The results of the development were validated by two expert validators, one practitioner validator and ten MA Al-Mansyurati NW Aik Bukak students as students' limited test validators. Quantitative data from the results of feasibility validation were analyzed by percentage formula. Qualitative data in the form of responses and suggestions for improvement from the validator are used as considerations to make revisions to the modules developed. In general, the validator's assessment of the results of the development obtained an average percentage of material expert validators 88.8%, product design expert validators 95%, practitioner validators 92%, and limited trials of students 85.28%. This shows that the developed module is very feasible to proceed to the effectiveness test phase. Thus it can be concluded that the contextually based modules are declared to be feasible with very good quality.